THE SOAKING EFFECT OF 100% SMALL WHITE GINGER EXTRACT ON THE VALUE OF THE FLEXURAL STRENGTH OF ACRYLIC BASE (Flexural Strength Value of Acrylic Base Using Acrylic Resin Heat Cured Type) - Nadya Islami; Debby Saputera; Rahmad Arifin (FKG Unlam, 2020)
Background: The denture base material that is widely used is heat cured acrylic resin. One of mechanical properties of acrylic resin that must be considered in the selection of the basic denture material is flexural strength. Flexural strength is needed, among others, to resist the chewing power that must be received by dentures. The commonly used denture cleanser is Alkaline peroxide. 100% small white ginger extract can be used as natural denture cleanser. Objective: This study aimed to compare the flexural strength of heat cured acrylic base which in soaked 100% small white ginger extract with Alkaline peroxide solution as artificial denture cleanser. Method: This study was a pure laboratory experimental study with post test only with control group design, using simple random sampling. The sample was rectangular with a size of 65x10x2,5 mm. The number of samples used was 24 heat cured resin acrylic which was divided into 3 immersion groups, 100% small ginger extract, Alkaline peroxide, and aquades. The immersion carried out for 3 days 19 hours 25 minutes, obtained from 5 minutes denture cleanser presentation every day for 3 years. Flexural strength was tested using a Universal Testing Machine 3 Point Bending. Result: The everage flexural strength value of heat cured acrylic resin after soaked in 100% small white ginger extract was 70,98, in Alkaline peroxide 87,37, and 91,05 in aquades. The data was annalyzed using parametric One Way ANOVA test and Post Hoc Bonferroni test. Conclusion: The flexural strength of heat cured acrylic resin that soaked in 100% small white ginger extract is smaller than Alkaline peroxide after immersed for 3 days 19 hours 25 minutes.